INTRA-ASEAN TRADE – GRAVITY MODEL AND SPATIAL HAUSMAN-TAYLOR APPROACH - Phung, Duy Quang; Pham, Anh Tuan; Nguyen, Thi Xuan Thu (Journal of International Economics and Management, 2018)
This paper examine determinants of intra-industry trade between Vietnam and Asean countries. By solving endogenous problem and applying Hausman-Taylor model for panel two-way dataset, we detect that export flows of Vietnam gravitate to neigboring countries and those with similar GDP. More importantly, the research indicates the existence of spatial-lag interaction.